IDENTIFICATION OF A NEW HIGH POPULATION OF NEWBORN WITH CURVES OWN RISK INTRAUTERINE GROWTH - Ticona Rendón, Manuel (2015)
OBJECTIVES: To quantify the increase in small for gestational age (SGA RN) to use the intrauterine growth curves of Tacna, and study their risk factors. MATERlAL AND METHODS: 15 739 infants in the Hipolito Unanue Hospital in Tacna were studied, from 1994 to 1999, using intrauterine growth curves (CIU) by weight, Lubchenco and Tacna, and identifying RN PEG further, which is called " new PEG ", studying its risk factors. The Perinatal Information System, odds ratio and chi square test was used. RESULTS: RN large for gestational age (RN GEG) decreased 15.6% to 9.5%, appropriate for gestational age (RN AEG) remained at 83.2% and 81.3% and RN PEG increased from 1.2% to 9.2%; This change was statistically significant. There were 1448 RN-PEG using our curve and 189 when using Lubchenco. The difference in 1259 RN (8% of the total population) corresponds to the "RN new PEG". Their risk factors were multiple pregnancy, heart disease, hypertensive disease of pregnancy, primiparity and urinary tract infection; and its risks, increased morbidity, nutritional metabolic disorders, infections, birth defects, moderate depression at birth and neonatal mortality. CONCLUSIONS: It is confirmed that Lubchenco curves overestimate the GEG subdimensionan to RN and RN PEG, being a bit fussy for our RN pattern. The new PEG group at high risk of morbidity and mortality. We recommend making and using own curves.